What Goes Around Comes Around: Myth and Male Trauma in Somali Diasporic Cinema. Issue 2 (4th March 2019) - Bick, Tenley
Abstract: Recent scholarship on African cinema has expanded the discourse's historical focus on Francophone West Africa to address other regions, transnational cinemas, and film media on the Continent and in its diasporas. Other African cinemas, however, continue to be overlooked. Through formal and narrative analysis of several films by Somali film-maker Abdisalam Aato, especially Xaaskayga Araweelo (My Wife Araweelo, 2006), this article examines the recent phenomenon of Somali narrative cinema as a nationalist cinema in the post-conflict Somali diaspora. Special focus on myth, masculinity, and Islamic morality demonstrates these films' renegotiation of traditional Somali culture, gender roles, and identity after the fall of the Somali nation-state. This article argues Aato's films constitute a destabilised discourse of Somali masculinity in the diaspora. It also argues that these films distinctly engage diasporic crises of identity through their exploration of misandry, expanding discourses on African cinema and diaspora aesthetics, in turn.